Impact of Drying Processes on the Nutritional Composition, Volatile Profile, Phytochemical Content and Bioactivity of Salicornia ramosissima J. Woods - Sheila C. Oliveira-Alves; Fábio Andrade; Inês Prazeres; Andreia B. Silva; Jorge Capelo; Bernardo Duarte; Isabel Caçador; Júlio Coelho; Ana Teresa Serra; Maria R. Bronze (MDPI AG, 2021)
Salicornia ramosissima J. Woods is a halophyte plant recognized as a promising natural ingredient and will eventually be recognized a salt substitute (NaCl). However, its shelf-life and applicability in several food matrices requires the use of drying processes, which may have an impact on its nutritional and functional value. The objective of this study was to evaluate the effect of oven and freeze-drying processes on the nutritional composition, volatile profile, phytochemical content, and bioactivity of S. ramosissima using several analytical tools (LC-DAD-ESI-MS/MS and SPME-GC-MS) and bioactivity assays (ORAC, HOSC, and ACE inhibition and antiproliferative effect on HT29 cells). Overall, results show that the drying process changes the chemical composition of the plant. When compared to freeze-drying, the oven-drying process had a lower impact on the nutritional composition but the phytochemical content and antioxidant capacity were significantly reduced. Despite this, oven-dried and freeze-dried samples demonstrated similar antiproliferative (17.56 mg/mL and 17.24 mg/mL, respectively) and antihypertensive (24.56 mg/mL and 18.96 mg/mL, respectively) activities. The volatile composition was also affected when comparing fresh and dried plants and between both drying processes: while for the freeze-dried sample, terpenes corresponded to 57% of the total peak area, a decrease to 17% was observed for the oven-dried sample. The oven-dried S. ramosissima was selected to formulate a ketchup and the product formulated with 2.2% (w/w) of the oven-dried plant showed a good consumer acceptance score. These findings support the use of dried S. ramosissima as a promising functional ingredient that can eventually replace the use of salt.